Extraction and Analysis of Beta-carotene Recovery in CPO and Oil Palm Waste by Using HPLC - Suria, Kupan; Hazrulrizawati, Hamid; Kulkarni, Ajaykumar D.; M. M., Yusoff (Asian Research Publishing Network (ARPN), 2016)
Beta-carotene is known to have a high demand in food industry which has made global industry to face challenges especially in fulfilling customers’ requirement that are looking for ‘‘environment friendly’’ and natural products. This has opened up wide opportunities in utilizing crude palm oil (CPO) and oil palm waste (OPW) as natural sources of beta-carotene. Thus, present study explains recovery of beta-carotene from CPO and OPW of palm pressed fiber (PPF) and empty fruit bunch (EFB). Initially, crude oil from solid OPW samples was extracted by soxhlet extraction. Then, recovered oil from both PPF and EFB along with CPO were used to extract palm carotene. Extraction of beta-carotene from CPO and OPW were performed by using soxhlet adsorption method. High performance liquid chromatography (HPLC) analysis revealed beta-carotene a a major carotene in extracted samples. Results obtained indicated that 3790 ppm of beta-carotene extracted from CPO, 1414 ppm from PPF and 702 ppm from EFB by this soxhlet adsorption method.